2013
DOI: 10.4067/s0301-732x2013000200002
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal microorganisms in cats and dogs: a brief review

Abstract: RESUMENEl tracto gastrointestinal (GI) de animales contiene diferentes tipos de microorganismos conocido como la microbiota GI. Por mucho tiempo, la microbiota GI ha generado interés porque los microorganismos GI están involucrados en múltiples procesos fisiológicos en el hospedero, así perpetuando salud o enfermedad. Estudios recientes han demostrado que la microbiota GI de gatos y perros es tan compleja como en humanos y otros animales, revelado con el uso de tecnologías de secuencia modernas y otras técnica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 100 publications
1
9
0
3
Order By: Relevance
“…The same condition has been found in human and cats IBD. These results underline the importance of those clusters of bacteria, which also produce SCFAs, in the maintenance of gastrointestinal health (Suchodolski et al, 2012;Garcia-Mazcorro and Minamoto, 2013).…”
Section: Dysbiosis Of the Gut Microbiota In Animal Diseasesupporting
confidence: 53%
“…The same condition has been found in human and cats IBD. These results underline the importance of those clusters of bacteria, which also produce SCFAs, in the maintenance of gastrointestinal health (Suchodolski et al, 2012;Garcia-Mazcorro and Minamoto, 2013).…”
Section: Dysbiosis Of the Gut Microbiota In Animal Diseasesupporting
confidence: 53%
“…However, Garcia-Mazcorro et al showed a more dominant presence of Firmicutes (75-98%) in the fecal community of dogs using 454-pyrosequencing (Garcia-Mazcorro et al, 2012). These observed discrepancies might be explained by the molecular method used, which should be considered when abundances of gut microbiota are compared among different studies (Garcia-Mazcorro and Minamoto, 2013). While the Firmicutes phylum strongly dominated the canine feces in the current study, with a relative abundance of 94.4%, the predominant bacterial phyla present in the PC and DC of the SCIME™ corresponded with the main bacterial phyla detected in the fecal material of the dogs, resulting in an average community composition along the simulated canine gastrointestinal tract of 50.5% Firmicutes, 34.5% Bacteroidetes, 7.4% Fusobacteria, 4.9% Actinobacteria and 2.7% Proteobacteria.…”
Section: Discussionmentioning
confidence: 97%
“…Bacterial 16S rRNA gene surveys have shown that, like other mammals, dogs and cats harbor complex GI microbial communities whose taxonomic compositions vary not only by diet but also factors such as age (Deusch et al., ), incidence of metabolic disorders (e.g., obesity, diabetes) (Bell et al., ; Handl et al., ; Park et al., ) and intestinal issues (e.g., IBD, diarrhea) (Guard et al., ; Suchodolski, Markel, et al., ; Suchodolski et al., ). In clinically healthy dogs and cats, Firmicutes and Bacteroidetes are generally the dominant phyla found in the fecal microbiome, with Fusobacteria, Actinobacteria, and Proteobacteria also featuring prominently (Deng & Swanson, ; Garcia‐Mazcorro & Minamoto, ). In the dog and cat, the general roles and functions of these bacterial phyla are assumed to be similar to their roles in the gut microbiota of model organisms such as humans and rodents, for which, more information is available.…”
Section: Characterization Of Dog and Cat Gi Microbiotamentioning
confidence: 99%